Գահաժառանգության խնդիրբ Բագրատունյաց Հայաստանում եւ գահակցության վարկածը - Արման Եղիազարյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В арменоведческих исследованиях было высказано мнение о том, что во время правления царя Армении Ашота III (953-977) его сын Смбат II (977-989) был соправителем царя. An opinion has been developed In Armenian Studies, according to which during the reign of Armenian king Ashot III (953-977) his son Smbat II (977-989) was coruler of the king.
Keywords: History